Pyroptosis-Related Gene Signature Predicts the Prognosis and Immune Infiltration in Neuroblastoma - Li, Wanrong; Li, Xin; Xia, Yuren; Wang, Jian (Frontiers in Genetics, 2022)
Neuroblastoma is the most common pediatric extracranial solid tumor. The five-year survival rate for high-risk neuroblastoma is less than 50%, despite multi-modal treatment. Pyroptosis, an inﬂammatory type of programmed cell death, manifested pro-tumor and anti-tumor roles in the adult tumor. Thus, we aim to elucidate the function of pyroptosis in neuroblastoma. We classified neuroblastoma patients into two clusters based on the pyroptosis gene expression. We found high pyroptosis neuroblastoma manifested favorable overall survival and more anti-tumor immune cells infiltration. Based on the results of a step-wise Cox regression analysis, we built a four-gene predictive model including NLRP3, CASP3, IL18, and GSDMB. The model showed excellent predictive performance in internal and external validation. Our findings highlight that high pyroptosis positively correlated with neuroblastoma outcomes and immune landscape, which may pave the way for further studies on inducing pyroptosis therapy in high-risk neuroblastoma treatment.